2022
DOI: 10.1108/cg-02-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

Managerial ability and informative earnings management: the role of CEO-commissioner relationship and board independence

Abstract: Purpose The purpose of this study is to examine the effect of managerial ability on informative earnings management (hereafter IEM) and to examine the moderating role of the chief executive officer and board of commissioner relationship (hereafter CEO-commissioner relationship) and board independence between managerial ability and IEM. Design/methodology/approach Sample consists of 864 firm-years listed on the Indonesian Stock Exchange. Informative earnings management is measured by the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
5
0
1
Order By: Relevance
“…The beneficial impact of earnings informativeness on company value was reinforced by managerial abilities. The study's findings supported those of Tucker and Zarowin (2006) and Putra (2022), who found that higher-quality information was provided to shareholders (firm value) and that informative earnings management was typically associated with skilled managers. The significant value of the size interaction variable as a control variable with managerial ability was 0.025> 0.005.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The beneficial impact of earnings informativeness on company value was reinforced by managerial abilities. The study's findings supported those of Tucker and Zarowin (2006) and Putra (2022), who found that higher-quality information was provided to shareholders (firm value) and that informative earnings management was typically associated with skilled managers. The significant value of the size interaction variable as a control variable with managerial ability was 0.025> 0.005.…”
Section: Resultssupporting
confidence: 81%
“…According to Lukita (2022), managerial ability had a positive effect on income quality. Putra (2022) stated that it increased informative earnings management. The study also evaluated the stewardship behavior of managers, who demonstrated a propensity to manage earnings in an informative manner and to give shareholders better information.…”
Section: Income Smoothing Earnings Informativeness Firm Value and Man...mentioning
confidence: 99%
See 1 more Smart Citation
“…Independent commissioners must also have a strong position in the company to enhance the effectiveness of the board of commissioners' oversight function (Alijoyo & Sirait, 2022). The study results by Putra (2023) show that the higher the level of independence of the board of commissioners, the stronger the oversight function of managers motivated by achieving their profits. This is supported by the study by Indriastuti et al (2020), who stated that because independent commissioners are thought to reduce agency conflicts, their proportion has a beneficial impact on business value (Bernhard & Veny, 2024;Hidayat & Muliasari, 2020).…”
Section: Literature Reviewmentioning
confidence: 90%
“…The manager's ability is considered an ability that can maximize the value of the company against the efficient use of limited resources during trading activities. Managers with high levels of knowledge and correct behavior have a higher industry understanding of the environment (Putra, 2023). According to agency theory, the practice of tax aggressiveness is a rational strategic action that can reduce the agency cost of a company.…”
Section: Agency Theorymentioning
confidence: 99%